Food and feeding habits of the greenback grey mullet Liza subviridis (Valenciennes, 1836) from Parangipettai waters, south-east coast of India - Ashiq Ur Rahman, M.; Lyla, P. S.; Ajmal Khan, S. (Indian Journal of Fisheries, 2016)
The feeding ecology and prey preference of greenback grey mullet Liza subviridis (Valenciennes, 1836) were investigated in Parangipettai waters (11°29′25.55″N; 79°45′38.62″E) from May 2011 to April 2012. A total of 328 male and 360 female specimens of L. subviridis were analysed. Detritus and sand particles formed the major food item of L. subviridis in both sexes besides, diatoms, dinoflagellates, algae, zooplankton, foraminiferans, polychaetes and larval forms were also noticed and ranked respectively based on the quantities. Feeding intensity showed that the percentage of ‘empty’ stomachs varied from 7.2% (November 2011) to 19.3% (August 2011) and from 7.1% (March 2012) to 19.2% (August 2011) in males and females respectively whereas the ‘gorged’ stomach in males and females was in the ranges of 4.6% (March 2012) - 14.5% (December 2011) and 4.6% (September 2011) - 14.5% (April 2012). The gastrosomatic index of males and females ranged between 5.9% (October 2011) - 8.2% (May 2011) and 6.1% (March 2012) - 8.1% (May 2011) respectively. The results agree with the previous reports and extend the understanding on its well-being, reproductive seasons and stock of L. subviridis in Parangipettai waters.